Kegiatan Meronce Menggunakan Barang Bekas untuk Meningkatkan Kemampuan Sosial-Emosional Anak Usia Dini - Senjaya, Fitria Aprilia; Nafiqoh, Heni; Nurunnisa, Rita (IKIP Siliwangi, 2025)
Teaching materials are a crucial component of the learning process. With appropriate teaching materials, learning activities can be conducted more effectively, particularly in supporting the development of children's social-emotional skills. To enhance these aspects, teachers often rely on classical approaches, which may not optimally stimulate children's social-emotional development. The purpose of this study was to improve children's social-emotional aspects, including patience, independence, responsibility, perseverance, and self-confidence. This study employed a qualitative descriptive method, with data collected through direct observation. The sample consisted of 15 children aged 4–5 years at Koner Siti Masitoh, observed over seven sessions. Data processing involved data reduction, data display, and conclusion. The results of the study showed an improvement in children's social-emotional development. In the initial condition, most children had not yet developed the targeted social-emotional skills. By the seventh session, their social-emotional development had progressed to the levels of “Developing as Expected” and “Developing Very Well.” This was evident in their behavior: initially, children were unwilling to follow rules, were impatient, and refused to complete their string-threading activities. However, by the seventh meeting, they were able to follow rules, showed greater patience during the string-threading tasks, and were willing to complete them independently. Bahan ajar adalah bagian terpenting dalam proses pembelajaran.dengan bahan ajar yang tepat, kegiatan pembelajaran akan berjalan efektif, khususnya untuk meningkatkan kemampuan sosial emosional anak. Untuk meningkatkan aspek sosial emosional anak, guru biasanya hanya menstimulasi dengan cara klasikal saja, sehingga aspek sosial emosional anak kurang terstimulus dengan maksimal. Tujuan penelitian ini adalah untuk meningkatkan aspek sosial emosional anak, diantaranya yaitu sabar, mandiri, tanggung jawab, pantang menyerah dan percaya diri. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data melalui observasi langsung, dengan sampel data anak usia 4-5 Tahun di Koner Siti Masitoh dengan jumlah 15 anak yang dilaksanakan selama tujuh kali pertemuan. Pengolahan data menggunakan reduksi data, penyaian data dan penarikan kesimpulan. Hasil penelitian menunjukan adanya peningkatan aspek sosial emosional pada anak yaitu pada kondsi awal, aspek sosial emosional rata-rata anak belum berkembang. Pada pertemuan ketujuh aspek sosial emosional anak meningkat menjadi berkembang sesuai harapan dan berkembang sangat baik. Hal ini dapat dilihat pada prilaku anak ketika kondisi awal anak tidak mau mengikuti aturan, tidak sabar dan tidak mau mengerjakan ronceannya sampai selesai, sedangkan pada pertemuan ketujuh anak menjadi mampu mengikuti aturan, lebih sabar saat membuat roncean dan mau mengerjakan ronceannya sampai selesai.